Numerical Study on the Influence of Inlet Blockage Ratios and Flow Conditions on Scour Development in Circular Culverts - Salam Hussein Sulaiman; Kaywan Othman Ahmed; Mohsen Isari; Jamil Bahrami (Journal of Studies in Civil Engineering, 2025)
This study evaluates the effectiveness of Flow-3D numerical simulations in predicting the scour profile, depth, and location downstream of circular culverts under varying flow conditions. Two hydrographs with peak flows of 13.8 l/s and 20 l/s were used to simulate unsteady flow conditions. Each hydrograph included seven different flow discharges, and steady flow tests were conducted at the maximum rates observed during the unsteady scenarios. This study examined circular culverts subjected to inlet blockages of 0%, 25%, and 50% and compared the numerical result from Flow-3D simulations utilizing the Renormalization Group (RNG) turbulence model with observed data. As a result, scour was consistently most significant at 0% blockage across all scenarios and all cases compared to nonblocked cases. Therefore, nonblocked numerical results in the unsteady first hydrograph showed 11.76% and 6.86% increases compared to 25% and 50% blockage, while experimental data indicated 6.97% and 6.45%. For the unsteady second hydrograph, nonblocked scour depths increased by 5.55% and 4.44% in simulations and 3.53% in experiments for both blockage levels. This pattern continued under steady flow conditions: in the first hydrograph, numerical results showed increases of 7.76% and 11.65%, and experimental data showed 8.33% and 11.45%. In the second hydrograph, scour increased numerically by 4.2% and 7.36% and experimentally by 7% and 8.23%.